Соціальні мережі як один з найефективніших засобів протидії інформаційній агресії в українському Інтернет-просторі - Семен, Наталія; Semen, Natalia; Семен, Наталия (Видавництво Львівської політехніки, 2017)
Проаналізовано специфіку роботи російських спільнот “Новости RT на русском” та “Россия 24: ФЕДЕРАЛЬНЫЕ НОВОСТИ” під час подачі контенту про події в Україні та у зоні АТО у соціальній мережі ВКонтакте. На противагу російським “паблікам”, досліджено специфіку подачі “постів” про події в зоні АТО українськими групами “УКРАЇНА LIVE – НОВИНИ ▪ АТО”, “Український простір”, “УКРОП | НОВИНИ УКРАЇНИ | АТО”. На основі ключових методів пропаганди, виокремлених досвідченими науковцями України та світу, автор аналізує їх застосування у контенті цих груп.

The article indicated by the specifics of the Russian social network VKontakte with the informational aggression by the Russian Federation in relation to Ukraine. Analyzed the activity of famous Ukrainian communities in the social networks that are struggling with information attack Russia. The analysis of patterns and trends of work VKontakte when submitting news about events in Ukraine, which cause resonance with the Russian side. Main objective is to analyze the efficiency of the Ukrainian community in the social network VKontakte when covering events in the ATO area and compare them with the work of Russian communities in the social network. To achieve the objectives of the study, we used the following methods: 1) a systematic approach – is to consider the interrelated elements of the system are developed in sequence and form a coherent whole; 2) Systems Analysis – for quantitative and qualitative analysis of information aggression problems in Ukraine; 3) information method – for systematization of information and scientific analysis, presentation and synthesis of new indicators. The problem of our study lies in the fact that today not all media workers realized the impact and power of social networks. Therefore, not every edition actively lead the community in social networks. It is therefore necessary to conduct master classes, training to combat aggression information through social networks.

Проанализирована специфика работы российских сообществ “Новости RT на русском” и “Россия 24: Федеральный НОВОСТИ” при подаче контента о событиях в Украине и в зоне АТО в социальной сети ВКонтакте. В противовес российским “Паблик” исследована специфика подачи “постов” о событиях в зоне АТО украинский группами “УКРАИНА LIVE – НОВОСТИ ▪ АТО”, “Украинское пространство”, “УКРОП | НОВОСТИ УКРАИНЫ | АТО ”. На основе ключевых методов пропаганды, выделен- ных опытными учеными Украины и мира, автор анализирует их применение в контенте этих групп.
Social networks as one of the most effective means of counteraction information aggression in the ukrainian Internet space
Социальные сети как одно из самых эффективных средств противодействия информационной агрессии в украинском Интернет-пространстве
Keywords: соціальні мережі; Інтернет-спільнота; група; паблік; інформаційна безпека; пропаганда; social networking; Internet community; public; information security; propaganda; социальные сети; интернет-сообщество; группа; паблик; инфор- мационная безопасность; пропаганда; 070; 316.472.4]; [323.266; 004.738.5] (477; 470)